MENINGKATKAN PRODUKSI FLAVAN-3-OL MELALUI KALUS Camellia sinensis L. DENGAN ELISATOR CU2+ - Sutini B; Tatik W; Wahyu W; Sutiman B. Sumitro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Flavan-3-ol is a secondary metabolite in tea plant that is used as anti obesity agent. The difficulty in obtaining Flavan-3-ol out of tea plant is due to dependency on season, need for large land, need for very intensive care and relatively low production. Therefore flavan 3-ol production needs tobe developed in vitro culture technique. This technique can cope with the handicapes above. It can effectively control production and requires less space. The purpose of this research was to enhance fl avan 3-ol production by modifyingmedium and precursor appropriately. The steps of this process were: (1) Callus induction through cultivating the tea shoot explants on medium fi lled with some growth hormone, (2) fl avan-3-ol induction on callus culture using Cu 2+ elicitor. (3) Observation over callus growth, (4) Observation over qualitative characterizes of flavan 3-ol. The result of the research using Cu 2+ elicitor shows that the production of flavan-3-ol increases by 12.5%.